Correlation and Regression Analysis of Various Viability and Vigour Parameters in Pearl millet [Pennisetum glaucum (L.) R. Br.] - HEMENDER,; VPS SANGWAN,; VS MOR,; SUSHMA SHARMA, (Seed Research, 2026)
Pearl millet is a small seeded crop which is chiefly grown in the Kharif season that is characterised by severe weather conditions. Therefore, uniform and good field emergence is very crucial for the success of the crop. A study was conducted to determine the correlation among various seed viability/ vigour parameters and their ability to predict the field emergence of forty-two genotypes of pearl millet, comprising of hybrids, their parents and other inbred lines. Nine seed vigour parameters víz. standard germination, test weight, seedling length, seedling dry weight, vigour index I, vigour index II, accelerated ageing test, electrical conductivity and field emergence were observed and the correlation between these parameters were calculated. Results revealed that all the seed vigour parameters significantly and positively correlated with each other except electrical conductivity, which showed negative correlation. Regression analysis was also performed for prediction of field emergence, with the help of other seed vigour parameters. Estimated mean of field emergence obtained by various viability and vigour parameters were at par with the actual value obtained. The maximum value of coefficient of regression (0.937) was obtained for standard germination, indicating the reliability of this test, followed by electrical conductivity (0.821), vigour index-I (0.743), vigour index-II (0.641) and accelerated ageing (0.559), as these tests were found to be highly correlated with field emergence.